2010
DOI: 10.4028/www.scientific.net/msf.667-669.421
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and Tensile Properties of Maraging Steel Processed by Equal-Channel Angular Pressing

Abstract: An 18Ni (C-250) maraging steel was successfully processed by equal channel angular pressing (ECAP) for a single pass at room temperature. Microstructural observations showed that the martensite laths of 18Ni maraging steel were elongated to more narrow bands with a width of 100-200 nm after ECAP deformation. After ageing treatment, many nano-sized precipitates distributed uniformly within the refined martensite lathes. In comparison with the tensile strength (1940 MPa) of general used steel (solution + aging t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The material preparation can be found in our previous work [6]. ECAP experiments were performed using a split die that could yield an effective strain of ~1 for a single pass [7], with two channels intersecting at inner angle of 90 o and outer angle of 30 o . The solidsolution rods in dimension of Φ16 mm × 80 mm lubricated with MoS 2 were processed through 1, 2, 4, 8, 12 and 16 passes (route B C [7]) at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The material preparation can be found in our previous work [6]. ECAP experiments were performed using a split die that could yield an effective strain of ~1 for a single pass [7], with two channels intersecting at inner angle of 90 o and outer angle of 30 o . The solidsolution rods in dimension of Φ16 mm × 80 mm lubricated with MoS 2 were processed through 1, 2, 4, 8, 12 and 16 passes (route B C [7]) at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous work [6][7][8], we reported that equal-channel angular pressing (ECAP) method was very effective in the refinement of the lath size, and lath width could be readily controlled during the multi-pass ECAP process. Accordingly, the yield strength of maraging steel was significantly enhanced by refining lath width down into nano-order via ECAP technique.…”
Section: Introductionmentioning
confidence: 99%